Dirac plasmon-assisted asymmetric hot carrier generation for room-temperature infrared detection - Alireza Safaei (Nature Portfolio, 2019)
Designing electronically asymmetric environment across monolayer graphene enhances the photo-thermoelectric effect and enables efficient infrared photodetection. Here, the authors report a photodetector based on CVD grown nano-patterned graphene with high responsivity of ~2900 V/W within 8–12 µm wavelength regime by Dirac plasmon-assisted hot carrier generation at room-temperature.